Centrality and Pricing in Spatially Differentiated Markets: The Case of Gasoline - Matthias Firgo; Dieter Pennerstorfer; Christoph Weiss (Austrian Institute of Economic Research (WIFO), 2012)
This paper highlights the importance of "centrality" for pricing. Firms characterised by a more central position in a spatial network are more powerful in terms of having a stronger impact on their competitors' prices and on equilibrium prices. These propositions are derived from a simple theoretical model and tested empirically for the retail gasoline market in Vienna (Austria). We compute different measures of network centrality by using information on the locations of gasoline stations in the road network. Results from a spatial autoregressive model confirm that the strategic interaction in pricing between competitors is significantly related to their degree of centrality.
Keywords: 330; Network centrality; Spatial differentiation; Gasoline prices; Preisdifferenzierung; Räumlicher Wettbewerb; Tankstelle; Monopolistischer Wettbewerb; Korrelation; Wien; Österreich